OP0066 Safety of Anti-TNFα Agents for the Treatment of Juvenile Idiopathic Arthritis-Related Uveitis: Data from the Orchidea Registry. (9th June 2015) - Ferrari, D.; Zannin, M.E.; Gerloni, V.; Pontikaki, I.; Bracaglia, C.; Cimaz, R.; Simonini, G.; Falcini, F.; Corona, F.; Viola, S.; Breda, L.; La Torre, F.; et al.
Abstract : Background: Chronic anterior uveitis (CAU) is the most frequent extra-articular complication of Juvenile Idiopathic Arthritis (JIA). To date, the treatment of this potentially sight-threatening condition is related to its severity and includes immunosuppressive drugs and biological agents. Due to the lack of information on the long-term safety and efficacy of Anti-TNFα Agents, namely Infliximab (IFX) and Adalimumab (ADA), since 2007 a National Registry (named ORCHIDEA ) was established and involved a multicenter interdisciplinary team formed by Paediatric Rheumatologists and Ophthalmologists. Since then, data were prospectively collected online through a protected website. We report the data on safety of Anti-TNFα Agents for the treatment of patients with JIA-CAU registered so far. Objectives: To report the long-term safety of anti-TNF agents in patients with JIA-related CAU included in the ORCHIDEA Registry . Methods: Since January 2007, patients with JIA and AU, diagnosed according to the SUN Working Group criteria, were managed by a standardized step-up protocol including topical treatment, systemic corticosteroid, immunosuppressive treatment and biological agents. Patients refractory to standard immunosuppressive treatment and/or corticosteroid-dependent treated with IFX and ADA entered the ORCHIDEA Registry . Data recorded online at least every three months were: uveitis and arthritis course, number/type of ocular structural complications, laboratory parameters, drug-related adverse events (AEs), treatment shift or withdrawal. Results: Up to December 2013, 24 Paediatric Rheumatology/Ophthalmology Centers were included in the Registry and reported 209 JIA-CAU patients treated with anti-TNFα agents. In particular, 131 patients received ADA, 78 received IFX as first anti-TNF agent. Treatment switch was reported in 49 patients (23.4%): 35 IFX to ADA, 4 ADA to IFX, 10 ADA to other biological agents.The length of follow-up was at least 2 years for 126 patients, 3 years for 89, 4 years for 62, 5 years 39. No major AEs were reported, 22.7% of patients experienced 72 minor AEs and in 9.9% they were multiple. Infections were reported in 34 patients, headache in 10, infusion reactions in 8, weight loss/loss in 4, gastrointestinal symptoms in 5, skin reactions in 5, irritability in 3, menometrorrhagy in 2. No significant difference in prevalence of AEs were observed in the two treatment groups. Conclusions: Anti-TNF treatment in JIA-CAU appears to be safe in the medium-term period. The ORCHIDEA Registry is an effective tool for prospective data collection which also helps the standardization of the clinical approach to the young patients with uveitis in a multidisciplinary setting. Acknowledgements: We acknowledge IL VOLO, no-profit Association for Rheumatic Diseases in Children, ONLUS, Padua, Italy for having supported ORCHIDEA Registry with a dedicated grant. Disclosure of Interest: None declared